Correlation between morphological characteristics in spectral‐domain‐optical coherence tomography, different functional tests and a patient's subjective handicap in acute central serous chorioretinopathy. Issue 7 (16th January 2018) - Gerendas, Bianca S.; Kroisamer, Julia‐Sophie; Buehl, Wolf; Rezar‐Dreindl, Sandra M.; Eibenberger, Katharina M.; Pablik, Eleonore; Schmidt‐Erfurth, Ursula; Sacu, Stefan
Abstract: Purpose: The purpose of this study was to identify quantitatively measurable morphologic optical coherence tomography (OCT) characteristics in patients with an acute episode of central serous chorioretinopathy (CSC) and evaluate their correlation to functional and psychological variables for their use in daily clinical practice. Methods: Retinal thickness (RT), the height, area and volume of subretinal fluid (SRF)/pigment epithelium detachments were evaluated using the standardized procedures of the Vienna Reading Center. These morphologic characteristics were compared with functional variables [best‐corrected visual acuity (BCVA), contrast sensitivity (CS), retinal sensitivity/microperimetry, fixation stability], and patients' subjective handicap from CSC using the National Eye Institute 25‐item Visual Function Questionnaire (NEI VFQ‐25). Results: Data from 39 CSC patients were included in this analysis. Three different SRF height measures showed a high negative correlation ( r  = −0.7) to retinal sensitivity within the central 9°, which was also negatively correlated with SRF area and volume ( r  = −0.6). The CS score and fixation stability (fixation points within 2°) showed a moderate negative correlation ( r  = −0.4) with SRF height variables. Comparison of the subjective handicap with morphological characteristics in spectral‐domain (SD)‐OCT showed SRF height had the highest correlation ( r  = −0.4) with the subjective problems reported and overall NEI VFQ‐25 score. Conclusion: In conclusion, SRF height measured in SD‐OCT showed the best correlation with functional variables and patients' subjective handicap caused by the disease and therefore seems to be the best variable to look at in daily clinical routine. Even though area and volume also show a correlation, these cannot be so easily measured as height and are therefore not suggested for daily clinical routine.